Temporal and spatial interactions of sympatric mesocarnivores at a Biosphere Reserve: coexistence or competition? - Carrera-Treviño, Rogelio; Astudillo-Sánchez, Claudia C.; Garza-Torres, Héctor A.; Martínez-García, Luis; SORIA-DÍAZ, LEROY (Revista de Biología Tropical, 2018)
Interspecific interactions among tropical mesocarnivorous species and other mammalian trophic guilds have been poorly studied, despite they have important implications in the survival, structure, demography, and distribution of these species. In this study we analyzed spatio-temporal interactions of three sympatric mesocarnivores that are located in the Northeastern limit of their geographic distribution in Mexico, with the objective of analyzing if these species coexist or compete in the axis of the temporal and spatial niche. With a sampling period from January 2015 to December 2016 and 26 camera-trapping stations (with in a set of two camera traps opposite to each other) and located along roads and animal trails, we determined the activity pattern and habitat use of L. wiedii (margay), L. pardalis (ocelote) y P. yagouaroundi (yaguarundi). All independent photographs of each species were grouped into three temporal categories (day, night and twilight) and six habitat categories; Oak Forest, Oak-Pine Forest, Cloud Forest, Pine-Oak Forest, Tropical Deciduous Forest and Medium Forest. Temporal and spatial overlap between species (i.e interactions) was obtained with the Czekanowski index and the Pianka index, respectively. These indices are symmetrical and take values from zero to one, where the results close to zero indicate that there is no overlap between species and values close to one indicate overlap. We obtained a total of 379 independent photographs, of which 239 corresponded to margay, 118 to ocelot and 22 to yaguarundi. Margay and ocelot were nocturnal, with 75 % of their records in this category showing a high temporal overlap (0.85); whereas yaguarundi was fully diurnal, suggesting it may be able to coexist with the other two species (margay and ocelot). Moreover, the yaguarundi used habitat similar to ocelot and margay (with high spatial overlap of 0.81 and 0.72, respectively), while the spatial overlap between the margay and ocelot was intermediate (0.53), since they used in most cases different habitat types. Our results suggest that there is no interspecific competition among these tropical mesocarnivorous species, probably due to antagonistic interactions among them on the temporal and spatial axis. These strategies may positively favor populations of mesocarnivores, which are characterized by having a high territorial behavior.